PERAN KINERJA APARATUR TERHADAP PELAYANAN PENERBITAN AKTA TANAH DI KANTOR KECAMATAN BARANTI KABUPATEN SIDENRENG RAPPANG - Risna; Ibrahim, Monalisa; Asad, Muh. Arisal (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study aims to examine the role of apparatus performance in the service process of land certificate issuance at the Baranti Subdistrict Office, Sidenreng Rappang Regency. The research employs a quantitative descriptive approach. The population consists of 77 residents from Baranti Subdistrict. The sampling technique used is probability sampling. Data collection methods include observation, questionnaire distribution, and literature review. The collected data are analyzed using quantitative descriptive analysis with the assistance of SPSS software, employing a Likert scale.